Zirconia sintered body and method for producing the same
Patent Information
- Application Number
- JP2024181469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-17
AI Technical Summary
【0034】 本発明によれば、安定化剤としてY2O3を含むジルコニア焼結体において、充分な機械的強度を有しており、且つ、透光性、透明性に優れたジルコニア焼結体を提供することができる。また、当該ジルコニア焼結体の製造方法を提供することができる。
Smart Images

Figure 0007631611000004 
Figure 0007631611000005 
Figure 0007631611000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a zirconia sintered body and a method for producing a zirconia sintered body. [Background technology]
[0002] Conventionally, efforts have been made to improve the mechanical strength, transparency (parallel light transmittance), and translucency (total light transmittance) of zirconia sintered bodies.
[0003] For example, Patent Document 1 discloses a translucent yttria-containing zirconia sintered body made of zirconia containing more than 4 mol% and not more than 7 mol% yttria, having a sintered body grain size of 2.0 μm or less, a relative density of 99.5% or more, and a total light transmittance of 40% or more for visible light with a wavelength of 600 nm at a thickness of 1 mm (Claim 1). It also discloses that the zirconia sintered body of this configuration achieves high translucency and strength (paragraph
[0011] ). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-222450 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in Patent Document 1, the crystal grain size is set to 0.4 μm or more (paragraph
[0016] ), and it is presumed that the zirconia sintered body does not have transparency. In other words, although it can be seen that the zirconia sintered body in Patent Document 1 has a certain degree of translucency and strength, it cannot be said to have transparency.
[0006] Thus, conventionally, sintered bodies having both mechanical strength and transparency or translucency have been obtained, but no zirconia sintered body having all of mechanical strength, transparency, and translucency has been obtained.
[0007] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a zirconia sintered body having sufficient mechanical strength and excellent translucency and transparency, and to provide a method for producing the zirconia sintered body. [Means for solving the problem]
[0008] The present inventors have conducted extensive research into the above-mentioned problems, and as a result have found that the above-mentioned problems can be solved by employing the following configuration, thereby completing the present invention.
[0009] The present invention provides the following: [1] A stabilized zirconia comprising zirconia and a stabilizer, The stabilizer comprises Y2O3, The content of the Y2O3 in the stabilized zirconia is more than 4.0 mol% and not more than 6.5 mol% in terms of oxide, The average crystal grain size is 100 nm or more and 200 nm or less, The monoclinic fraction is 0.5% or less, The tetragonal fraction is 20.0% or more and 96.0% or less, The cubic fraction is 4.0% or more and 80.0% or less, A zirconia sintered body having a relative sintered density of 99.6% or more.
[0010] In order to improve transparency, a method of suppressing scattering at grain boundaries is considered. In order to suppress scattering at grain boundaries, it is effective to reduce the number of grain boundaries per unit thickness, that is, to increase the crystal grain size. However, if the crystal grain size is increased to a level at which transparency is obtained, the mechanical strength is reduced. Therefore, in the present invention, the average crystal grain size is set to 200 nm or less, and high mechanical strength is maintained while other methods, namely, "scattering at grain boundaries" and "scattering at residual pores", are suppressed to achieve transparency and translucency. There are two types of "scattering at grain boundaries": scattering at the interface between tetragonal phases / tetragonal phases, and scattering at the interface between tetragonal phases / cubic phases. In order to suppress "scattering at grain boundaries", the inventors have conceived of 1. increasing the ratio of the cubic phase, which is an optically isotropic body, and 2. suppressing scattering at the tetragonal phase by reducing the crystal grain size. Regarding the above "1.", according to the present invention, the content of Y2O3 in the stabilized zirconia exceeds 4.0 mol% in terms of oxide, so that the cubic phase ratio can be 4.0% or more. Since the cubic phase ratio is 4.0% or more, scattering at grain boundaries can be suppressed, and translucency can be improved. In addition, since the content of Y2O3 is 6.5 mol% or less in terms of oxide, the mechanical strength is excellent. Regarding the above point "2," according to the present invention, since the average crystal grain size is 100 nm or more and 200 nm or less, grains having a grain size smaller than the visible light wavelength are present, and the effect of scattering at grain boundaries is reduced. Furthermore, since the cubic phase ratio is 4.0% or more, scattering of the tetragonal phase is suppressed, and transparency in particular is improved. Furthermore, in the present invention, since the relative sintered density is 99.6% or more, "scattering due to residual pores" is suppressed, and high light transmittance and transparency are obtained. In addition, when the Y2O3 content is in the range of more than 4.0 mol% to 6.5 mol% in terms of oxide, the tetragonal phase fraction and the cubic phase fraction are in a trade-off relationship, and the higher the Y2O3 content, the higher the cubic phase fraction but the lower the tetragonal phase fraction. The lower the Y2O3 content, the higher the tetragonal phase fraction but the lower the cubic phase fraction. In addition, since the content of the Y2O3 in the stabilized zirconia exceeds 4.0 mol % in terms of oxide, the monoclinic fraction can be made 0.5% or less. The more monoclinic phase is contained, the more the mechanical strength and transparency decrease. On the other hand, according to the present invention, the monoclinic phase ratio is 0.5% or less, and therefore the mechanical strength and transparency are excellent.
[0011] As described above, according to the above-mentioned configuration, it is possible to provide a zirconia sintered body having sufficient mechanical strength and excellent translucency and transparency.
[0012] Furthermore, the present invention provides the following: [2] The zirconia sintered body according to [1], characterized in that the content of the Y2O3 in the stabilized zirconia exceeds 5.2 mol% in terms of oxide.
[0013] When the content of the Y2O3 in the stabilized zirconia exceeds 5.2 mol % in terms of oxide, the cubic phase ratio is easily made to be 40.0% or more.
[0014] Furthermore, the present invention provides the following: [3] The tetragonal fraction is 20.0% or more and 60.0% or less, The zirconia sintered body according to [1] above, characterized in that the cubic phase ratio is 40.0% or more and 80.0% or less.
[0015] When the cubic fraction is 40.0% or more, scattering at grain boundaries can be further suppressed, and light transmittance can be further improved.
[0016] Furthermore, the present invention provides the following: [4] The content of the Y2O3 in the stabilized zirconia is more than 5.2 mol% in terms of oxide, The tetragonal fraction is 20.0% or more and 60.0% or less, The zirconia sintered body according to [1] above, characterized in that the cubic phase ratio is 40.0% or more and 80.0% or less.
[0017] When the content of the Y2O3 in the stabilized zirconia exceeds 5.2 mol % in terms of oxide, the cubic phase ratio is easily made to be 40.0% or more. Furthermore, when the cubic fraction is 40.0% or more, scattering at grain boundaries can be further suppressed, and light transmittance can be further improved.
[0018] Furthermore, the present invention provides the following: [5] The zirconia sintered body according to any one of [1] to [4], characterized in that it contains Al2O3 in a range of 0.15 mass% or less based on the entire zirconia sintered body.
[0019] When Al2O3 is contained in the entire zirconia sintered body, it functions as a sintering aid, resulting in excellent low-temperature sintering properties. Also, if the Al2O3 content is 0.15 mass% or less, scattering due to the precipitated phase (grain boundary) of alumina (impurity) is reduced, so that high translucency and transparency can be maintained.
[0020] Furthermore, the present invention provides the following: [6] The zirconia sintered body according to any one of [1] to [5], characterized in that the total light transmittance at a thickness of 1 mm is 45% or more and 60% or less.
[0021] A total light transmittance of 45% or more at a thickness of 1 mm can be said to be excellent in light transmittance.
[0022] Furthermore, the present invention provides the following: [7] The zirconia sintered body according to any one of [1] to [6], characterized in that the parallel light transmittance at a thickness of 1 mm is 7.0% or more and 30.0% or less.
[0023] A parallel light transmittance of 7.0% or more at a thickness of 1 mm can be said to be excellent in transparency.
[0024] Furthermore, the present invention provides the following: [8] The zirconia sintered body according to any one of [1] to [7], characterized in that the three-point bending strength is 500 MPa or more and 1000 MPa or less.
[0025] A three-point bending strength of 500 MPa or more can be said to be high strength.
[0026] Furthermore, the present invention provides the following: [9] The toughness value by the IF method is 2.7 MPa m 0.5 More than 5.0MPa m0.5 The zirconia sintered body according to any one of the items [1] to [8], characterized in that:
[0027] The toughness value by the IF method is 2.7MPa m 0.5 If it is equal to or greater than this, it can be said to have high toughness.
[0028] Furthermore, the present invention provides the following:
[10] Zirconia powder was mixed at 1.0 t / cm 2 More than 2.5t / cm 2 A process A of molding the molded body at a pressure of A step B of pre-sintering the molded body under normal pressure at a temperature of 1150° C. or higher and 1250° C. or lower for 1 hour or longer and 5 hours or shorter to obtain a pre-sintered body; and a step C of sintering the pre-sintered body under conditions of a pressure of 50 MPa or more and 200 MPa or less, 1150°C or more and 1250°C or less, and a time of 1 hour or more and 5 hours or less to obtain a sintered body.
[0029] According to the above-mentioned configuration, the molded body is pre-sintered under relatively low temperature conditions of 1150°C to 1250°C for 1 hour to 5 hours under normal pressure, so that a pre-sintered body with suppressed grain growth can be obtained. Since grain growth is suppressed, it is possible to obtain a zirconia sintered body with high transparency.
[0030] According to the above configuration, the molded body is pre-sintered under normal pressure at 1150°C to 1250°C for 1 hour to 5 hours, so that the particles of the zirconia powder are appropriately bonded together during the pre-sintering process, and the pores (gaps between the particles of the zirconia powder) in the molded body can be made into closed pores. In other words, the pre-sintering can change the pores from a state in which the pores are connected to each other (open pores) to isolated closed pores surrounded by bonds of the zirconia powder. The temporary sintered body, which has closed pores, is then sintered under conditions of a pressure of 50 MPa to 200 MPa, 1150°C to 1250°C, and 1 hour to 5 hours, so that the closed pores can be almost completely eliminated. Specifically, the pressure applied during sintering compresses the closed pores to their minimum size, and the element diffusion (element flow) during sintering pushes the pores out of the sintered body, so that the closed pores can be almost completely eliminated. By removing the pores, the total light transmittance (translucency) and parallel light transmittance (transparency) can be improved. If the pores in the pre-sintered body are not closed pores, the pores cannot be removed even if the main sintering is performed under conditions of a pressure of 50 MPa to 200 MPa, a temperature of 1150°C to 1250°C, and a time of 1 hour to 5 hours. This is because if the pores in the pre-sintered body are not closed pores, pressure is not easily transmitted to the pores during main sintering.
[0031] Whether or not the pores in the provisionally sintered body are closed pores can be determined by whether or not the relative sintered density can be measured by the Archimedes method. If the pores are open pores, the pores will absorb water during measurement, making it impossible to measure the relative sintered density (the measured value will be abnormal). In other words, if the relative sintered density can be measured (the value is within the expected range), it can be determined that the pores are closed pores.
[0032] According to the above-mentioned configuration, the pre-sintered body is sintered under the conditions of a pressure of 50 MPa to 200 MPa, 1150°C to 1250°C, and 1 hour to 5 hours, so that the relative sintered density can be 99.6% or more. If the pre-sintered body is not formed and the molded body is directly sintered, that is, if step C is performed after step A without performing step B, it is not possible to achieve a relative sintered density of 99.6% or more while maintaining the average crystal grain size of 100 to 200 nm.
[0033] In this specification, the term "preliminary sintered body" refers to a sintered body having a relative sintered density of 92% or more and less than 99.5%. In addition, in this specification, the term "preliminary sintering" refers to sintering so that the relative sintered density of the sintered body is in the range of 92% or more and less than 99.5%. Effect of the Invention
[0034] According to the present invention, it is possible to provide a zirconia sintered body containing Y2O3 as a stabilizer, which has sufficient mechanical strength and is excellent in translucency and transparency. Also, it is possible to provide a method for producing the zirconia sintered body. [Brief description of the drawings]
[0035] [Figure 1] FIG. 2 is a schematic diagram for explaining a method for producing a zirconia powder according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram for explaining an indentation length and a crack length. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to these embodiments. In this specification, zirconia (zirconium oxide) is a general term, and contains 10 mass % or less of impurity metal compounds including hafnia. In addition, in this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "substantially consists of" and "consist only of".
[0037] The maximum and minimum values of the content of each component shown below are independently the preferred minimum and maximum values of the present invention, regardless of the contents of other components. Furthermore, the maximum and minimum values of various parameters (measured values, etc.) shown below are independently preferred minimum and maximum values of the present invention, regardless of the content (composition) of each component.
[0038] [Zirconia sintered body] Hereinafter, an example of the zirconia sintered body according to the present embodiment will be described. However, the zirconia sintered body of the present invention is not limited to the following example.
[0039] The zirconia sintered body according to this embodiment is The stabilized zirconia includes zirconia and a stabilizer. The stabilizer comprises Y2O3, The content of the Y2O3 in the stabilized zirconia is more than 4.0 mol% and not more than 6.5 mol% in terms of oxide, The average crystal grain size is 100 nm or more and 200 nm or less, The monoclinic fraction is 0.5% or less, The tetragonal fraction is 20.0% or more and 96.0% or less, The cubic fraction is 4.0% or more and 80.0% or less, The relative sintered density is 99.6% or more.
[0040] As described above, the zirconia sintered body according to this embodiment contains stabilized zirconia.
[0041] The content of the stabilized zirconia is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, when the entire zirconia sintered body is taken as 100% by mass. The content of the stabilized zirconia can be 99% by mass or less, 98% by mass or less, etc., when the entire zirconia sintered body is taken as 100% by mass. In addition, the zirconia sintered body may be composed of only the stabilized zirconia. In other words, the zirconia sintered body may be composed of only the stabilized zirconia sintered. In this case, the content of the stabilized zirconia is 100% by mass, when the entire zirconia sintered body is taken as 100% by mass. The content of the stabilized zirconia is preferably 70 mass% or more and 99 mass% or less, more preferably 80 mass% or more and 99 mass% or less, even more preferably 90 mass% or more and 98 mass% or less, and particularly preferably 95 mass% or more and 98 mass% or less, when the entire zirconia sintered body is taken as 100 mass%.
[0042] The stabilized zirconia contains zirconia and a stabilizer.
[0043] The total content of zirconia and the stabilizer in the stabilized zirconia is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, when the entire stabilized zirconia is taken as 100% by mass. The total content of zirconia and the stabilizer can be 99% by mass or less, 98% by mass or less, etc., when the entire stabilized zirconia is taken as 100% by mass. The stabilized zirconia may be composed only of zirconia and the stabilizer. In this case, the total content of zirconia and the stabilizer is 100% by mass, when the entire content of the stabilized zirconia is taken as 100% by mass. The total content of zirconia and stabilizer in the stabilized zirconia, when the entire stabilized zirconia is taken as 100 mass%, is preferably 70 mass% or more and 99 mass% or less, more preferably 80 mass% or more and 99 mass% or less, even more preferably 90 mass% or more and 98 mass% or less, and particularly preferably 95 mass% or more and 98 mass% or less.
[0044] The stabilizer includes Y2O3.
[0045] The content of the Y2O3 in the stabilized zirconia is more than 4.0 mol % and not more than 6.5 mol % in terms of oxide. Since the content of Y2O3 in the stabilized zirconia exceeds 4.0 mol% in terms of oxide, the cubic phase ratio can be 4.0% or more. Since the cubic phase ratio is 4.0% or more, scattering at grain boundaries can be suppressed, and translucency can be improved. In addition, since the content of Y2O3 is 6.5 mol% or less in terms of oxide, the mechanical strength is excellent. In addition, when the Y2O3 content is in the range of more than 4.0 mol% to 6.5 mol% in terms of oxide, the tetragonal phase fraction and the cubic phase fraction are in a trade-off relationship, and the higher the Y2O3 content, the higher the cubic phase fraction but the lower the tetragonal phase fraction. The lower the Y2O3 content, the higher the tetragonal phase fraction but the lower the cubic phase fraction. In addition, since the content of the Y2O3 in the stabilized zirconia exceeds 4.0 mol % in terms of oxide, the monoclinic fraction can be made 0.5% or less. The more monoclinic phase is contained, the lower the mechanical strength and transparency become. On the other hand, the zirconia sintered body has a monoclinic phase ratio of 0.5% or less, and therefore has excellent mechanical strength and transparency.
[0046] The content of the Y2O3 in the stabilized zirconia is preferably more than 5.2 mol %, and more preferably 5.3 mol % or more, calculated as the oxide. The content of the Y2O3 in the stabilized zirconia is preferably 6.4 mol % or less, and more preferably 6.3 mol % or less, calculated as the oxide. The content of the Y2O3 in the stabilized zirconia is preferably more than 5.2 mol % and not more than 6.4 mol %, more preferably not less than 5.3 mol % and not more than 6.3 mol %, calculated as the oxide.
[0047] The stabilizer may further include other stabilizers other than Y2O3. The other stabilizers are not particularly limited, but examples thereof include Yb2O3, Er2O3, CeO2, Sc2O3, Nd2O3, La2O3, Tb2O3, CaO, etc. These other stabilizers may be included alone or in combination of two or more.
[0048] When a stabilizer other than Y2O3 is contained, the content is preferably within a range that does not significantly affect the transparency and translucency. When a stabilizer other than Y2O3 is contained, the content of the other stabilizer in the stabilized zirconia is preferably 0.01 mol % or more and 2.5 mol % or less in terms of oxide. The content of the other stabilizer in the stabilized zirconia is more preferably 0.05 mol % or more, and even more preferably 0.10 mol % or more, calculated as oxide. The content of the other stabilizers in the stabilized zirconia is more preferably 2.0 mol % or less, and even more preferably 1.5 mol % or less, calculated as oxide. The content of the other stabilizers in the stabilized zirconia is more preferably 0.05 mol % or more and 2.0 mol % or less in terms of oxide, and further preferably 0.10 mol % or more and 1.5 mol % or less in terms of oxide.
[0049] The total amount of stabilizers in the stabilized zirconia is preferably 4.1 mol% or more and 6.5 mol% or less in terms of oxide. When the total amount of stabilizers is 4.1 mol% or more in terms of oxide, the monoclinic phase ratio can be further reduced. Also, when the total amount of stabilizers is 6.5 mol% or less in terms of oxide, the cubic phase ratio, which has low mechanical properties (strength, toughness), can be reduced, and the tetragonal phase ratio, which has high mechanical properties, can be increased.
[0050] The total amount of the stabilizer is more preferably 4.5 mol % or more, further preferably 5.0 mol % or more, and particularly preferably 5.2 mol % or more, calculated as oxide. The total amount of the stabilizer is more preferably 6.4 mol % or less, further preferably 6.3 mol % or less, particularly preferably 6.0 mol % or less, calculated as oxide. The total amount of the stabilizers is more preferably 4.5 mol % to 6.4 mol %, further preferably 5.0 mol % to 6.3 mol %, particularly preferably 5.2 mol % to 6.0 mol %, calculated as oxide.
[0051] The content of zirconia in the stabilized zirconia is preferably 80% by mass or more and 99% by mass or less, more preferably 85% by mass or more and even more preferably 90% by mass or more, more preferably 98% by mass or less and even more preferably 97% by mass or less. The content of zirconia in the stabilized zirconia is more preferably 85% by mass or more and 98% by mass or less, and further preferably 90% by mass or more and 97% by mass or less.
[0052] The zirconia sintered body preferably contains Al2O3 (alumina) in the range of 0.15 mass% or less based on the entire zirconia sintered body. When Al2O3 is contained in the entire zirconia sintered body, it functions as a sintering aid, and has excellent low-temperature sintering properties. In addition, if the content of Al2O3 is 0.15 mass% or less, scattering due to the precipitation phase (grain boundary) of alumina (impurity) is reduced, so that translucency and transparency can be maintained at a high level.
[0053] When the zirconia sintered body contains Al2O3, the content of Al2O3 is more preferably 0.01 mass% or more, and further preferably 0.05 mass% or more. In the case where the zirconia sintered body contains Al2O3, the content of Al2O3 is more preferably 0.13 mass% or less, and further preferably 0.10 mass% or less. When the zirconia sintered body contains Al2O3, the content of Al2O3 is more preferably 0.01 mass % or more and 0.13 mass % or less, and further preferably 0.05 mass % or more and 0.10 mass % or less.
[0054] The zirconia sintered body may contain, in addition to alumina, sinterable ceramics, thermosetting resins, etc., for the purpose of improving properties such as strength.
[0055] The zirconia sintered body may contain at least one selected from the group consisting of Fe, V, Mn, Co, Zn, Cu, and Ti within a range that does not significantly affect transparency and translucency. When the zirconia sintered body contains at least one selected from the group consisting of Fe, V, Mn, Co, Zn, Cu, and Ti as a coloring element, the zirconia sintered body can be suitably colored.
[0056] The form of the coloring element is not particularly limited, and it can be added in the form of an oxide, a chloride, etc. Specific examples of colorants containing the coloring element include Fe2O3, V2O5, MnO2, CoO, ZnO, CuO, TiO2, etc.
[0057] When Fe2O3 is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.05% by mass or more and 0.5% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0058] When V2O5 is contained as the colorant, the content is preferably 0.005% by mass or more and 0.5% by mass or less, and more preferably 0.01% by mass or more and 0.1% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0059] When MnO2 is contained as the colorant, the content is preferably 0.005% by mass or more and 2% by mass or less, and more preferably 0.1% by mass or more and 1.1% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0060] When CoO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 2% by mass or less, and more preferably 0.01% by mass or more and 1.5% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0061] When ZnO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.1% by mass or more and 0.5% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0062] When CuO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.05% by mass or more and 0.6% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0063] When TiO2 is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 2% by mass or less, more preferably 0.01% by mass or more and 1% by mass or less, and even more preferably 0.1% by mass or more and 0.3% by mass or less, when the entire zirconia sintered body is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0064] The zirconia sintered body has an average crystal grain size of 100 nm or more and 200 nm or less. Since the average crystal grain size is 100 nm or more and 200 nm or less, particles having a grain size smaller than the visible light wavelength are present, and the effect of scattering at the grain boundary is reduced. In addition, as described below, since the cubic phase ratio is 4.0% or more, scattering of the tetragonal phase is suppressed, and transparency in particular is improved.
[0065] The average crystal grain size is preferably 195 nm or less, and more preferably 190 nm or less. The average crystal grain size is preferably 110 nm or more, and more preferably 120 nm or more. The average crystal grain size is preferably 110 nm or more and 195 nm or less, and more preferably 120 nm or more and 190 nm or less. The average crystal grain size can be controlled, for example, by adjusting the sintering conditions (particularly the sintering temperature) when sintering the zirconia powder. The method for determining the average crystal grain size is the method described in the Examples.
[0066] The monoclinic fraction contained in the crystal phase of the zirconia sintered body is 0.5% or less. The more monoclinic phase is contained, the lower the mechanical strength and transparency. Since the zirconia sintered body has a monoclinic fraction of 0.5% or less, it has excellent mechanical strength and transparency.
[0067] The monoclinic fraction is preferably 0.3% or less, and more preferably 0.2% or less. The smaller the monoclinic fraction, the more preferable it is, and it is, for example, 0.05% or more, 0.1% or more. The monoclinic fraction is preferably 0.05% or more and 0.3% or less, and more preferably 0.1% or more and 0.2% or less. The monoclinic fraction can be controlled by, for example, the content of a stabilizer (particularly Y2O3) or the like. The method for determining the monoclinic fraction is the method described in the Examples.
[0068] The tetragonal phase ratio contained in the crystal phase of the zirconia sintered body is 20.0% or more and 96.0% or less. The more the tetragonal phase is contained, the more the mechanical strength is improved. The zirconia sintered body has a tetragonal phase ratio of 20% or more, and therefore has excellent mechanical strength. In addition, the zirconia sintered body has a tetragonal phase ratio of 96.0% or less, and therefore scattering of the tetragonal phase is suppressed, and the transparency in particular is improved.
[0069] The tetragonal phase ratio is preferably 60.0% or less, more preferably 58.0% or less, and further preferably 55.0% or less. The tetragonal phase ratio is preferably 25.0% or more, more preferably 30.0% or more, and further preferably 32.0% or more. The tetragonal phase ratio is preferably 25.0% or more and 60.0% or less, more preferably 30.0% or more and 58.0% or less, and further preferably 32.0% or more and 55.0% or less. The tetragonal phase ratio can be controlled by, for example, the content of a stabilizer (particularly Y2O3) or the like. The tetragonal phase ratio is determined by the method described in the Examples.
[0070] The cubic crystalline phase of the zirconia sintered body has a cubic crystalline phase ratio of 4.0% or more and 80.0% or less. The cubic crystalline phase does not have optical anisotropy (has optical isotropy), so when the cubic crystalline phase ratio is increased, the total light transmittance (translucency) is improved. On the other hand, the cubic crystalline phase has a property of being prone to grain growth, so when the cubic crystalline phase ratio is increased too much, the crystal grains become large, and the parallel light transmittance (transparency) decreases. Since the cubic crystalline phase ratio of the zirconia sintered body is 4.0% or more, scattering at grain boundaries can be suppressed, and the translucency can be improved. In addition, since the cubic crystalline phase ratio of the zirconia sintered body is 80.0% or less, grain growth can be suppressed, and the parallel light transmittance can be maintained high.
[0071] The cubic phase ratio is preferably 75.0% or less, more preferably 70.0% or less, and further preferably 68.0% or less. The cubic phase ratio is preferably 40.0% or more, more preferably 42.0% or more, and even more preferably 45.0% or more. The cubic phase ratio is preferably 40.0% or more and 75.0% or less, more preferably 42.0% or more and 70.0% or less, and even more preferably 45.0% or more and 68.0% or less. The cubic phase ratio can be controlled, for example, by the content of a stabilizer (particularly Y2O3). The cubic phase ratio is determined by the method described in the Examples.
[0072] The crystal planes of the zirconia sintered body are non-oriented. This is evident from the fact that no orientation can be confirmed in the XRD spectrum of the zirconia sintered body and that a molding / sintering method that orients the crystal planes is not adopted in the manufacturing method of the zirconia sintered body described later.
[0073] <Relative sintered density> The relative sintered density of the zirconia sintered body is 99.6% or more. Since the relative sintered density of the zirconia sintered body is 99.6% or more, scattering in residual pores is suppressed, and high light transmittance and transparency are obtained. In addition, since the relative sintered density of the zirconia sintered body is 99.6% or more, it can be said to have high strength. The relative sintered density is preferably 99.7% or more, and more preferably 99.8% or more. The higher the relative sintered density, the more preferable it is, for example, 99.95% or less, 99.9% or less. The relative sintered density is preferably 99.7% or more and 99.95% or less, and more preferably 99.8% or more and 99.9% or less.
[0074] <Method for measuring the relative sintered density of zirconia sintered body> The relative sintered density is represented by the following formula (1). Relative sintered density (%) = (sintered density / theoretical sintered density) × 100 (1) Here, the theoretical sintered density (ρ0) is a value calculated by the following formula (2-1). ρ0=100 / [(Y / 3.987)+(100-Y) / ρz]···(2-1) Here, ρz is a value calculated by the following formula (2-2). ρz = [124.25(100-X) + [molecular weight of stabilizer] × X] / [150.5(100+X)A 2 C]···(2-2) Here, the molecular weight of the stabilizer is 225.81 for Y2O3. Additionally, X and Y are the stabilizer concentration (mol %) and the alumina concentration (wt %), respectively, and A and C are values calculated by the following formulas (2-3) and (2-4), respectively. A=0.5080+0.06980X / (100+X)...(2-3) C=0.5195-0.06180X / (100+X)...(2-4) In formula (1), the theoretical sintered density varies depending on the powder composition. For example, the theoretical sintered density of yttria-containing zirconia is 6.117 g / cm when the yttria content is 2 mol%. 3 , 3 mol% is 6.098 g / cm 3 , 5.5 mol% is 6.051 g / cm 3 (when Al2O3 = 0 wt%). In addition, the theoretical sintered density (ρ1) when other components (stabilizers, colorants, etc.) other than alumina are included is: ρ1=100 / [(Z / V)+(100-Z) / ρ0]···(2-5) Z is the concentration of other components other than alumina (wt%), and V is the theoretical density of other components other than alumina (g / cm 3 ). The theoretical density of the other components other than alumina is 9.17 g / cm for Yb2O3. 3 , Er2O3 is 8.64g / cm 3 , CeO2 is 7.22g / cm 3 , Sc2O3 is 3.86g / cm 3 , Nd2O3 is 7.24g / cm 3 , La2O3 is 6.51g / cm 3 , Tb2O3 is 7.81g / cm 3 , CaO is 3.34g / cm 3 , Fe2O3 is 5.24g / cm 3 , ZnO is 5.61 g / cm 3 , MnO2 is 5.03g / cm 3 , CoO is 6.10g / cm 3 , Cr2O3 is 5.22g / cm 3 , TiO2 is 4.23g / cm 3 , CuO is 6.31g / cm3 , V2O5 is 3.36g / cm 3 Let us assume that. The sintered density is measured by the Archimedes method.
[0075] <Total light transmittance> The zirconia sintered body preferably has a total light transmittance of 45% or more and 60% or less at a thickness of 1 mm. When the zirconia sintered body has a total light transmittance of 45% or more at a thickness of 1 mm, it can be said to have excellent translucency.
[0076] The total light transmittance is preferably 46.0% or more, and more preferably 48.0% or more. The higher the total light transmittance, the more preferable it is, and for example, 59.0% or less, 58.0% or less. The total light transmittance is preferably 46.0% or more and 59.0% or less, and more preferably 48.0% or more and 58.0% or less. The total light transmittance is determined by the method described in the Examples.
[0077] <Parallel light transmittance> The zirconia sintered body preferably has a parallel light transmittance of 7.0% or more and 30.0% or less at a thickness of 1 mm. When the zirconia sintered body has a parallel light transmittance of 7.0% or more at a thickness of 1 mm, it can be said to have excellent transparency.
[0078] The parallel light transmittance is preferably 8.0% or more, and more preferably 10.0% or more. The higher the parallel light transmittance, the more preferable it is, and for example, 29.0% or less, 28.0% or less. The parallel light transmittance is preferably 8.0% or more and 29.0% or less, and more preferably 10.0% or more and 28.0% or less. The parallel light transmittance is determined by the method described in the Examples.
[0079] <Mechanical strength> The zirconia sintered body preferably has a three-point bending strength of 500 MPa or more and 1000 MPa or less.
[0080] The three-point bending strength is more preferably 550 MPa or more, and further preferably 600 MPa or more. The higher the three-point bending strength, the more preferable it is, but it can be, for example, 900 MPa or less, 850 MPa or less, etc. The three-point bending strength is more preferably 550 MPa or more and 900 MPa or less, and further preferably 600 MPa or more and 850 MPa or less.
[0081] When the three-point bending strength is 500 MPa or more, it can be said that the strength is higher. The three-point bending strength is determined by the method described in the Examples.
[0082] <Toughness> The zirconia sintered body has a toughness value of 2.7 MPa m 0.5 More than 5.0MPa m 0.5 It is preferable that:
[0083] The toughness value is more preferably 2.8 MPa m 0.5 More preferably, 3.0 MPa m 0.5 The toughness value is preferably as large as possible, for example, 4.8 MPa m 0.5 Below, 4.6MPa m 0.5 It can be as follows etc. The toughness value is more preferably 2.8 MPa m 0.5 More than 4.8MPa m 0.5 Less than or equal to 3.0 MPa m 0.5 More than 4.6MPa m 0.5 The following is the result.
[0084] The toughness value is 2.7 MPa m 0.5 The toughness value is determined by the method described in the Examples.
[0085] <Hydrothermal degradation resistance> The zirconia sintered body preferably has a monoclinic fraction of 2.0% or less after hydrothermal treatment at 134°C and 0.3 MPa (absolute pressure 0.3 MPa) for 75 hours. If the monoclinic fraction after the hydrothermal treatment is 2.0% or less, it can be said to have better resistance to hydrothermal deterioration. The monoclinic fraction after the hydrothermal treatment can be controlled, for example, by the amount of Y2O3 added or the average crystal grain size.
[0086] The monoclinic fraction after the hydrothermal treatment is more preferably 1.7% or less, and further preferably 1.5% or less. The smaller the monoclinic fraction after the hydrothermal treatment, the more preferable it is, and is, for example, 0.1% or more, 0.2% or more. The monoclinic fraction after the hydrothermal treatment is more preferably 0.2% or more and 1.7% or less, further preferably 0.1% or more and 1.5% or less, and particularly preferably 0% or more and 1.5% or less.
[0087] The zirconia sintered body according to this embodiment is not particularly limited, but can be obtained, for example, by using a zirconia powder described later and a method for producing a zirconia sintered body described later.
[0088] The zirconia sintered body according to the present embodiment can be used as an industrial part, an aesthetic part, a dental material, etc. More specifically, it can be used for jewelry, watch parts, watch dials, artificial teeth, molding parts, wear-resistant parts, chemical-resistant parts, etc.
[0089] [Zirconia powder] The zirconia powder according to this embodiment is The stabilized zirconia includes zirconia and a stabilizer. The stabilizer comprises Y2O3, The content of the Y2O3 in the stabilized zirconia is more than 4.0 mol % and not more than 6.5 mol % in terms of oxide.
[0090] The zirconia powder according to this embodiment can be used in the method for producing a zirconia sintered body described later.
[0091] The zirconia powder contains primary particles mainly composed of zirconia. All or a part of the primary particles are aggregated to form secondary particles. That is, the zirconia powder contains non-aggregated primary particles and secondary particles formed by aggregation of the primary particles. However, in the zirconia powder, the amount of primary particles that do not become secondary particles and exist in the form of non-aggregated primary particles is very small, for example, less than 1 mass% of the total primary particles (the total of non-aggregated primary particles and primary particles that have aggregated to become secondary particles). In other words, the zirconia powder may contain a very small amount of non-aggregated primary particles, but the majority is composed of secondary particles. Incidentally, "zirconia as the main component" means that the primary particles contain 70% by mass or more of zirconia when the primary particles are taken as 100% by mass. That is, in this specification, the primary particles containing zirconia as the main component refer to primary particles containing 70% by mass or more of zirconia. The content of zirconia contained in the primary particles is preferably 74% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more.
[0092] As described above, the zirconia powder according to this embodiment contains stabilized zirconia.
[0093] The content of the stabilized zirconia is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, when the entire zirconia powder is taken as 100% by mass. The content of the stabilized zirconia can be 99% by mass or less, 98% by mass or less, etc., when the entire zirconia powder is taken as 100% by mass. The zirconia powder may be composed only of the stabilized zirconia. In other words, the zirconia powder may be composed of only the stabilized zirconia sintered. In this case, the content of the stabilized zirconia is 100% by mass, when the entire zirconia powder is taken as 100% by mass. The content of the stabilized zirconia, when the entire zirconia powder is taken as 100 mass%, is preferably 70 mass% or more and 99 mass% or less, more preferably 80 mass% or more and 99 mass% or less, even more preferably 90 mass% or more and 98 mass% or less, and particularly preferably 95 mass% or more and 98 mass% or less.
[0094] The stabilized zirconia contains zirconia and a stabilizer.
[0095] The total content of zirconia and the stabilizer in the stabilized zirconia is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, when the entire stabilized zirconia is taken as 100% by mass. The total content of zirconia and the stabilizer can be 99% by mass or less, 98% by mass or less, etc., when the entire stabilized zirconia is taken as 100% by mass. The stabilized zirconia may be composed only of zirconia and the stabilizer. In this case, the total content of zirconia and the stabilizer is 100% by mass, when the entire content of the stabilized zirconia is taken as 100% by mass. The total content of zirconia and stabilizer in the stabilized zirconia, when the entire stabilized zirconia is taken as 100 mass%, is preferably 70 mass% or more and 99 mass% or less, more preferably 80 mass% or more and 99 mass% or less, even more preferably 90 mass% or more and 98 mass% or less, and particularly preferably 95 mass% or more and 98 mass% or less.
[0096] The stabilizer includes Y2O3.
[0097] The content of the Y2O3 in the stabilized zirconia is more than 4.0 mol % and not more than 6.5 mol % in terms of oxide. Since the content of Y2O3 in the stabilized zirconia exceeds 4.0 mol% in terms of oxide, the cubic phase ratio of the sintered body obtained by sintering the zirconia powder can be 4.0% or more. Since the cubic phase ratio of the sintered body obtained by sintering the zirconia powder is 4.0% or more, scattering at grain boundaries can be suppressed and translucency can be improved. In addition, since the content of Y2O3 is 6.5 mol% or less in terms of oxide, the sintered body obtained by sintering the zirconia powder has excellent mechanical strength. In addition, since the content of the Y2O3 in the stabilized zirconia exceeds 4.0 mol% in terms of oxide, the monoclinic fraction of the sintered body obtained by sintering the zirconia powder can be made 0.5% or less. The more monoclinic phase is contained, the lower the mechanical strength and transparency become. On the other hand, the sintered body obtained by sintering the zirconia powder has a monoclinic phase ratio of 0.5% or less, and therefore has excellent mechanical strength and transparency.
[0098] The content of the Y2O3 in the stabilized zirconia is preferably more than 5.2 mol %, and more preferably 5.3 mol % or more, calculated as the oxide. The content of the Y2O3 in the stabilized zirconia is preferably 6.4 mol % or less, and more preferably 6.3 mol % or less, calculated as the oxide. The content of the Y2O3 in the stabilized zirconia is preferably more than 5.2 mol % and not more than 6.4 mol %, more preferably not less than 5.3 mol % and not more than 6.3 mol %, calculated as the oxide.
[0099] The stabilizer may further include other stabilizers other than Y2O3. The other stabilizers are not particularly limited, but examples thereof include Yb2O3, Er2O3, CeO2, Sc2O3, Nd2O3, La2O3, Tb2O3, CaO, etc. These other stabilizers may be included alone or in combination of two or more.
[0100] When a stabilizer other than Y2O3 is contained, the content is preferably within a range that does not significantly affect the transparency and translucency of the sintered body obtained by sintering the zirconia powder. When a stabilizer other than Y2O3 is contained, the content of the other stabilizer in the stabilized zirconia is preferably 0.01 mol % or more and 2.5 mol % or less in terms of oxide. The content of the other stabilizer in the stabilized zirconia is preferably, in terms of oxide, It is preferably 0.05 mol % or more, and more preferably 0.10 mol % or more. The content of the other stabilizer in the stabilized zirconia is preferably, in terms of oxide, It is preferably 2.0 mol % or less, and more preferably 1.5 mol % or less. The content of the other stabilizer in the stabilized zirconia is preferably, in terms of oxide, The content is preferably 0.05 mol % or more and 2.0 mol % or less, and more preferably 0.10 mol % or more and 1.5 mol % or less in terms of oxide.
[0101] The total amount of stabilizers in the stabilized zirconia is preferably 4.1 mol% or more and 6.5 mol% or less in terms of oxide. When the total amount of stabilizers is 4.1 mol% or more in terms of oxide, the monoclinic phase ratio can be further reduced. Also, when the total amount of stabilizers is 6.5 mol% or less in terms of oxide, the cubic phase ratio, which has low mechanical properties (strength, toughness), can be reduced, and the tetragonal phase ratio, which has high mechanical properties, can be increased.
[0102] The total amount of the stabilizer is more preferably 4.5 mol % or more, further preferably 5.0 mol % or more, and particularly preferably 5.2 mol % or more, calculated as oxide. The total amount of the stabilizer is more preferably 6.4 mol % or less, further preferably 6.3 mol % or less, particularly preferably 6.0 mol % or less, calculated as oxide. The total amount of the stabilizers is more preferably 4.5 mol % or more and 6.4 mol % or less, further preferably 5.0 mol % or more and 6.4 mol % or less, particularly preferably 5.2 mol % or more and 6.0 mol % or less, calculated as oxide.
[0103] The content of zirconia in the stabilized zirconia is preferably 80% by mass or more and 99% by mass or less, more preferably 85% by mass or more and even more preferably 90% by mass or more, more preferably 98% by mass or less and even more preferably 97% by mass or less. The content of zirconia in the stabilized zirconia is more preferably 85% by mass or more and 98% by mass or less, and further preferably 90% by mass or more and 97% by mass or less.
[0104] The zirconia powder preferably contains Al2O3 (alumina) in the range of 0.15 mass% or less based on the entire zirconia powder. When Al2O3 is contained in the entire zirconia powder, it functions as a sintering aid, and is excellent in low-temperature sintering properties. Furthermore, if the content of Al2O3 is 0.15 mass% or less, scattering due to the precipitated phase (grain boundary) of alumina (impurity) in the sintered body obtained by sintering the zirconia powder is reduced, so that the translucency and transparency can be maintained at a high level.
[0105] When the zirconia powder contains Al2O3, the content of Al2O3 is more preferably 0.01 mass % or more, and further preferably 0.05 mass % or more. When the zirconia powder contains Al2O3, the content of Al2O3 is more preferably 0.13 mass % or less, and further preferably 0.10 mass % or less. When the zirconia powder contains Al2O3, the content of Al2O3 is more preferably 0.01 mass % or more and 0.13 mass % or less, and further preferably 0.05 mass % or more and 0.10 mass % or less.
[0106] The zirconia powder may contain, in addition to alumina, sinterable ceramics, thermosetting resins, and the like, for the purpose of improving properties such as strength.
[0107] The zirconia powder may contain at least one element selected from the group consisting of Fe, V, Mn, Co, Zn, Cu, and Ti within a range that does not significantly affect transparency and translucency. When the zirconia powder contains at least one element selected from the group consisting of Fe, V, Mn, Co, Zn, Cu, and Ti as a coloring element, the zirconia sintered body obtained by sintering the zirconia powder can be suitably colored.
[0108] The form of the coloring element is not particularly limited, and it can be added in the form of oxide, chloride, etc. Specific examples of colorants containing the coloring element include Fe2O3, V2O5, MnO2, CoO, ZnO, CuO, TiO2, etc. The colorant is preferably added to the zirconia powder as a mixture.
[0109] When Fe2O3 is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.05% by mass or more and 0.5% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0110] When V2O5 is contained as the colorant, the content is preferably 0.005% by mass or more and 0.5% by mass or less, and more preferably 0.01% by mass or more and 0.1% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0111] When MnO2 is contained as the colorant, the content is preferably 0.005% by mass or more and 2% by mass or less, and more preferably 0.1% by mass or more and 1.1% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0112] When CoO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 2% by mass or less, and more preferably 0.01% by mass or more and 1.5% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0113] When ZnO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.1% by mass or more and 0.5% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0114] When CuO is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 1% by mass or less, and more preferably 0.05% by mass or more and 0.6% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0115] When TiO2 is included as the colorant, the content of the colorant is preferably 0.005% by mass or more and 2% by mass or less, more preferably 0.01% by mass or more and 1% by mass or less, and even more preferably 0.1% by mass or more and 0.3% by mass or less, when the entire zirconia powder is taken as 100% by mass. When the content of the colorant is 0.005% by mass or more, it is easy to obtain the intended coloring. In other words, it is easy to adjust the color tone.
[0116] <Pore distribution> 1. Peak top diameter of primary particle gap The zirconia powder preferably has a peak top diameter of 20 nm to 85 nm in the pore volume distribution in the range of 10 nm to 200 nm in the pore distribution based on the mercury intrusion method. The peak top diameter is preferably 25 nm or more, more preferably 30 nm, even more preferably 32 nm, and particularly preferably 35 nm or more. The peak top diameter is preferably 65 nm or less, more preferably 60 nm or less, even more preferably 57 nm or less, and particularly preferably 54 nm or less. In addition, when there are multiple peaks in the range of 10 nm or more and 200 nm or less in the pore distribution, the phrase "the peak top diameter of the pore volume distribution is 20 nm or more and 85 nm or less" in this specification means that all peak top diameters in the range of 10 nm or more and 200 nm or less in the pore distribution are within the range of 20 nm or more and 85 nm or less.
[0117] 2.Pore distribution width between primary particles The zirconia powder preferably has a pore distribution width of 40 nm to 105 nm in the range of 10 nm to 200 nm in the pore distribution based on mercury intrusion porosimetry. The pore distribution width is preferably 43 nm or more, more preferably 46 nm or more, even more preferably 50 nm or more, and particularly preferably 55 nm or more. The pore distribution width is preferably 100 nm or less, more preferably 95 nm or less, even more preferably 90 nm or less, particularly preferably 85 nm or less, and especially preferably 80 nm or less. Here, the pore distribution width refers to the width of the peak at which the log differential pore volume is 0.1 ml / g or more. In addition, when there are multiple peaks in the pore distribution in the range of 10 nm or more and 200 nm or less, in this specification, "the pore distribution width is 40 nm or more and 105 nm or less" means that, in a graph showing the pore distribution with pore diameter on the horizontal axis and log differential pore volume on the vertical axis, the point where the pore diameter first crosses the log differential pore volume of 0.1 mL / g (the point where the pore diameter crosses while ascending) as viewed from the smaller pore diameter side, the point where the pore diameter crosses the log differential pore volume of 0.1 mL / g again (the point where the pore diameter crosses while descending) is taken as the minimum diameter, and the difference between the maximum diameter and the minimum diameter is 40 nm or more and 105 nm or less.
[0118] 3.Pore volume between primary particles The zirconia powder preferably has a pore volume of 0.2 ml / g or more and less than 0.5 ml / g in the range of 10 nm or more and 200 nm or less in the pore distribution based on mercury intrusion porosimetry. The total pore volume is preferably 0.22 ml / g or more, more preferably 0.25 ml / g or more, even more preferably 0.3 ml / g or more, particularly preferably 0.35 ml / g or more, and especially preferably 0.4 ml / g or more. The total pore volume is preferably 0.48 ml / g or less, more preferably 0.46 ml / g or less, and particularly preferably 0.44 ml / g or less.
[0119] The "range of 10 nm or more and 200 nm or less in the pore distribution based on mercury intrusion porosimetry" is the range in which pores can exist as gaps between primary particles of the zirconia powder. In the range of 10 nm or more and 200 nm or less in the pore distribution based on mercury intrusion porosimetry, when the peak top diameter of the pore volume distribution is 20 nm or more and 85 nm or less and the pore distribution width is 40 nm or more and 105 nm or less, the size of each pore (the gap between each primary particle) is small and uniform (the distribution is sharp). Therefore, the primary particles constituting the secondary particles are uniformly and densely aggregated, and no large pores exist. Here, zirconia particles (including primary and secondary particles) have the characteristic that they are difficult to sinter if their pore volume is large. In other words, in order to sinter at low temperatures, not only must the size of the pores originating from the gaps between primary particles in the secondary particles be small and have a sharp distribution, but the pore volume originating from the gaps between primary particles must also be small at the same time. Therefore, when the pore volume in the range of 10 nm or more and 200 nm or less in the pore distribution based on mercury intrusion porosimetry is 0.2 ml / g or more and less than 0.5 ml / g, the pore volume originating from the gaps between primary particles is small and a configuration is obtained in which no large pores exist, making it possible to obtain a sintered body with a high sintered density.
[0120] <Particle size D 50 > The particle diameter D of the zirconia powder 50 The particle diameter D is preferably 0.1 μm or more and 0.7 μm or less. 50 is preferably 0.12 μm or more, more preferably 0.14 μm or more, further preferably 0.16 μm or more, and particularly preferably 0.2 μm or more. 50 is preferably 0.62 μm or less, more preferably 0.55 μm or less, further preferably 0.48 μm or less, particularly preferably 0.4 μm or less, particularly preferably 0.3 μm or less, and especially preferably less than 0.3 μm. The particle diameter D of the zirconia powder 50 When the particle size is 0.7 μm or less, the particle size of the secondary particles is relatively small, so that the gaps between the secondary particles can be made small. As a result, the low-temperature sintering property is excellent. In addition, since the gaps between the secondary particles are small, a sintered body with a high sintering density can be obtained.
[0121] <Specific surface area> The specific surface area of the zirconia powder is 20 m 2 / g or more 60m 2 The specific surface area is preferably 22 m / g or less. 2 / g or more, more preferably 24m 2 / g or more, more preferably 30m 2 / g or more, particularly preferably 35m 2The specific surface area is preferably 57 m 2 / g or less, more preferably 54m 2 / g, more preferably 52m 2 / g, particularly preferably 49m 2 / g.
[0122] The zirconia powder was prepared by cold isostatic pressing (CIP) at 2.0 t / cm 2 When molding is performed under this pressure, the relative molding density is preferably 40% or more and 55% or less. Here, the relative molding density is a value calculated by the following formula (3). Relative molded density (%) = (molded density / theoretical sintered density) × 100 (3) The theoretical sintered density (ρ0) is a value calculated by the formula (2-1) explained in the above section "Method for measuring the relative sintered density of a zirconia sintered body." 2.0t / cm using cold isostatic pressing method 2 When the zirconia powder is molded at a pressure of 1.0 t / cm, the relative molding density is easily set to 40% or more and 55% or less. 2 More than 2.5t / cm 2 By subjecting the molded body molded under the pressure described below to preliminary sintering in step B described below and main sintering in step C described below, it is possible to obtain a zirconia sintered body having an average crystal grain size of 100 nm to 200 nm, a monoclinic fraction of 0.5% or less, a tetragonal fraction of 20.0% to 96.0%, a cubic fraction of 4.0% to 80.0%, and a relative sintered density of 99.6% or more.
[0123] The relative molding density is more preferably 43.0% or more, and further preferably 45.0% or more. The relative molding density is more preferably 50.0% or less, and further preferably 48.0% or less. The relative molding density is more preferably 40% or more and 48% or less, further preferably 43.0% or more and 50.0% or less, and particularly preferably 45.0% or more and 48.0% or less. The relative molding density refers to a value obtained by the method described in the Examples.
[0124] The zirconia powder according to this embodiment has been described above.
[0125] [Method of manufacturing zirconia powder] An example of a method for producing a zirconia powder will be described below, however, the method for producing a zirconia powder is not limited to the following example.
[0126] The method for producing the zirconia powder according to this embodiment is as follows: Step 1: heating the zirconium salt solution and the sulfating agent solution separately to a temperature of 95° C. or higher and 100° C. or lower; a step 2 of contacting the heated zirconium salt solution with the heated sulfating agent solution so that the concentration of the mixed solution does not change from the start to the end of the contact, thereby obtaining a basic zirconium sulfate-containing reaction solution as a mixed solution; Step 3: aging the reaction solution containing basic zirconium sulfate obtained in step 2 at 95° C. or higher for 3 hours or more; A step 4 of adding a stabilizer to the basic zirconium sulfate-containing reaction liquid after aging obtained in the step 3; Step 5 of obtaining a zirconium-containing hydroxide by adding an alkali to the basic zirconium sulfate-containing reaction liquid obtained in step 4; Step 6: heat-treating the zirconium-containing hydroxide obtained in step 5 to obtain zirconia powder. Including, In the step 2, the SO4 in the mixed liquid is 2- The / ZrO2 weight ratio is maintained in the range of 0.3 to 0.8, and the temperature of the mixture is maintained at 95°C or higher. Each step will be described in detail below.
[0127] <Process 1> In step 1, the zirconium salt solution and the sulfating agent solution, which are starting materials, are each heated separately to a temperature of 95° C. or higher and 100° C. or lower. The zirconium salt used to prepare the zirconium salt solution may be any that supplies zirconium ions, and may be, for example, zirconium oxynitrate, zirconium oxychloride, zirconium nitrate, etc. These may be used alone or in combination of two or more. Among these, zirconium oxychloride is preferred in terms of high productivity on an industrial scale.
[0128] The solvent used to prepare the zirconium salt solution may be selected depending on the type of zirconium salt, etc. Usually, water (pure water, ion-exchanged water, the same applies below) is preferred.
[0129] The concentration of the zirconium salt solution is not particularly limited, but generally, it is preferably contained in an amount of 5 to 250 g, more preferably 20 to 150 g, calculated as zirconium oxide (ZrO2) per 1000 g of solvent.
[0130] The sulfating agent may be any agent that reacts with zirconium ions to produce sulfates (i.e., a sulfating agent), and examples thereof include sodium sulfate, potassium sulfate, ammonium sulfate, potassium hydrogen sulfate, sodium hydrogen sulfate, potassium disulfate, sodium disulfate, and sulfur trioxide. The sulfating agent may be in any form, such as a powder or a solution, but a solution (particularly an aqueous solution) is preferred. The solvent may be the same as that used to prepare the zirconium salt solution.
[0131] The acid concentration of the zirconium salt solution is preferably 0.1 to 2.0 N. By setting the acid concentration within the above range, the aggregation state of the particles constituting the zirconia powder can be controlled to a suitable state. The acid concentration can be adjusted by using, for example, hydrochloric acid, nitric acid, sodium hydroxide, etc.
[0132] The concentration of the sulfating agent (the sulfating agent solution) is not particularly limited, but it is generally preferable that the amount of the sulfating agent is 5 to 250 g, and particularly 20 to 150 g, per 1000 g of solvent.
[0133] The materials of the containers for preparing the zirconium salt solution and the sulfating agent solution are not particularly limited as long as they have a capacity capable of sufficiently stirring the zirconium salt solution and the sulfating agent solution, respectively, but it is preferable that the containers have a heating device capable of appropriately heating the solutions so that the temperatures of the solutions do not fall below 95°C. The heating temperature of the zirconium salt solution and the sulfating agent solution may be from 95° C. to 100° C., and is preferably at least 97° C. If step 2 is performed while the temperatures of the zirconium salt solution and the sulfating agent solution are below 95° C., the zirconium salt solution and the sulfating agent do not react sufficiently, resulting in a reduced yield.
[0134] <Process 2> In step 2, the heated zirconium salt solution and the heated sulfating agent solution are brought into contact with each other so that the concentration of the mixed solution does not change from the start to the end of the contact, thereby obtaining a basic zirconium sulfate-containing reaction solution as a mixed solution. 2- The / ZrO2 weight ratio is maintained in the range of 0.3 to 0.8, and the temperature of the mixture is maintained at 95°C or higher. Step 2 will now be described with reference to the drawings.
[0135] Fig. 1 is a schematic diagram for explaining the method for producing zirconia powder according to the present embodiment. As shown in Fig. 1, a container 10 is connected to one end (left side in Fig. 1) above a T-shaped pipe 20 via a valve 12. A container 30 is connected to the other end (right side in Fig. 1) above the T-shaped pipe 20 via a valve 32. A zirconium solution heated to 95°C or more and 100°C or less is stored in the container 10. A sulfating agent solution heated to 95°C or more and 100°C or less is stored in the container 30. In step 2, valve 12 is opened as well as valve 32, thereby bringing the zirconium solution into contact with the sulfating agent solution. The mixed liquid (basic zirconium sulfate-containing reaction liquid) obtained by the contact immediately flows into the aging vessel 40 from the bottom of the T-tube 20. In step 2, this method is used to prevent the concentration of the reaction liquid (concentration of the reaction liquid in the T-tube 20) from changing from the start to the end of the contact between the zirconium solution and the sulfating agent solution. In step 2, the concentration of SO4 2- / ZrO2 concentration change is suppressed, so a uniform reaction product is obtained. By adopting this process (Process 2), the peak top diameter, pore volume, and pore distribution width of the primary particles can be controlled. SO4 in the mixture in step 2 2- The weight ratio of SO4 / ZrO2 is preferably in the range of 0.3 to 0.8, more preferably 0.4 to 0.7, and further preferably 0.45 to 0.65. 2- By setting the weight ratio of SO4 to ZrO2 at 0.3 or more, the yield of basic zirconium sulfate, which is the reaction product, can be increased. 2- By setting the / ZrO2 weight ratio to 0.8 or less, it is possible to suppress the generation of soluble salts of zirconium sulfate and to suppress a decrease in the yield of basic zirconium sulfate. In step 2, in order to maintain the temperature of the mixed liquid at 95° C. or higher, it is preferable to install heaters in the pipes (eg, T-shaped pipe 20) for supplying each solution.
[0136] An example of step 2 will now be described in detail. When a T-shaped tube having a tube diameter L1 of 10 mm at one upper end (left side in FIG. 1), a tube diameter L2 of 10 mm at the other upper end (right side in FIG. 1), and a lower tube diameter L3 of 15 mm is used as the T-shaped tube 20, and 213 g of a 25 mass% aqueous sodium sulfate solution is contacted with 450 g of a 16 mass% aqueous zirconium oxychloride solution calculated as ZrO2, the time (contact time) from the start of the contact to the end of the contact (until the aqueous zirconium chloride solution in container 10 and the sulfating agent solution in container 30 are exhausted) is preferably 30 to 300 seconds, more preferably 60 to 200 seconds, and even more preferably 90 to 150 seconds.
[0137] <Process 3> In step 3, the basic zirconium sulfate-containing reaction liquid obtained in step 2 is aged at 95° C. or higher for 3 hours or more. In step 3, for example, the basic zirconium sulfate-containing reaction liquid flowing into the aging vessel 40 is aged at 95° C. or higher for 3 hours or more while being stirred by the stirrer 42. The upper limit of the aging time is not particularly limited, but is, for example, 7 hours or less. The temperature (aging temperature) of the mixed liquid (basic zirconium sulfate-containing reaction liquid) in step 3 is preferably 95° C. or higher, more preferably 97° C. or higher and 100° C. or lower. By setting the aging temperature to 95° C. or higher and the aging time to 3 hours or more, basic zirconium sulfate can be sufficiently produced and the yield can be increased. The mixture contains basic zirconium sulfate as a main component and is a basic zirconium sulfate slurry.
[0138] <Step 4> In step 4, a stabilizer is added to the basic zirconium sulfate-containing reaction liquid after aging obtained in step 3.
[0139] <Process 5> In step 5, an alkali is added to the basic zirconium sulfate-containing reaction liquid obtained in step 4 to carry out a neutralization reaction. By the neutralization, a zirconium-containing hydroxide is produced. The alkali is not limited, and examples thereof include caustic soda, sodium carbonate, ammonia, hydrazine ammonium hydrogen carbonate, etc. The concentration of the alkali is not particularly limited, but it is usually diluted with water to 5 to 30%. There are two methods for adding an alkali: (1) adding an alkali solution to a basic zirconium sulfate-containing reaction liquid; and (2) adding a basic zirconium sulfate-containing reaction liquid to an alkali solution. Either method may be used without any particular limitation. After neutralization, the slurry is filtered to obtain a zirconium-containing hydroxide. If necessary, the zirconium-containing hydroxide is preferably washed with pure water or the like to remove impurities. After washing with water, drying or the like can be performed as necessary.
[0140] <Process 6> In step 6, the zirconium-containing hydroxide obtained in step 5 is heat-treated (calcined) to oxidize the zirconium-containing hydroxide, thereby obtaining zirconia powder. The heat treatment temperature (calcination temperature) and heat treatment time (calcination time) of the zirconium-containing hydroxide are not particularly limited, but are usually performed at about 600 to 1050°C for 1 to 10 hours. The calcination temperature is more preferably 650°C or higher and 1000°C or lower, and even more preferably 700°C or higher and 980°C or lower. The calcination temperature is more preferably 2 to 6 hours, and even more preferably 2 to 4 hours. By setting the heat treatment temperature to 600°C or higher and 1000°C or lower, the specific surface area of the obtained zirconia powder can be made within a suitable range (20 m 2 / g or more 80m 2 / g or less). By setting the heat treatment temperature to 600° C. or more and 1050° C. or less, the pore distribution of the obtained zirconia powder can be set in a suitable range. The heat treatment atmosphere is not particularly limited, but it is usually performed in air or an oxidizing atmosphere.
[0141] <Process 7> After step 6, the obtained zirconia powder may be pulverized to form a slurry, if necessary. At that time, a binder may be added to improve moldability. When the zirconia powder is not slurried (pulverized), the binder and the zirconia powder may be mixed uniformly in a kneader. The binder is preferably an organic binder, since the organic binder can be easily removed from the molded body in a heating furnace in an oxidizing atmosphere and a degreased body can be obtained, so that impurities are less likely to remain in the final sintered body. The organic binder may be soluble in alcohol or soluble in a mixture of two or more selected from the group consisting of alcohol, water, aliphatic ketones, and aromatic hydrocarbons. The organic binder may be, for example, at least one selected from the group consisting of polyethylene glycol, glycol fatty acid ester, glycerin fatty acid ester, polyvinyl butyral, polyvinyl methyl ether, polyvinyl ethyl ether, and vinyl propionate. The organic binder may further include one or more thermoplastic resins that are insoluble in alcohol or the mixture. After the organic binder is added, the mixture is dried, pulverized, and otherwise treated by a known method to obtain the desired zirconia powder. By the grinding in step 7, for example, the particle diameter D of the zirconia powder is 50 For example, the zirconia powder obtained in step 5 can be pulverized according to its state to control the particle diameter D of the zirconia powder. 50 can be controlled.
[0142] When a sintering aid (e.g., alumina) or the like is added, it is possible to obtain zirconia powder containing the sintering aid, etc., by adding and mixing after the step 6. As a more detailed mixing method, it is preferable to disperse the zirconia in pure water or the like to form a slurry and wet mix it. When the step 7 is carried out, a sintering aid or the like may be added.
[0143] The zirconia powder according to this embodiment has been described above.
[0144] [Method of manufacturing zirconia sintered body] An example of a method for producing a zirconia sintered body will be described below. However, the method for producing a zirconia sintered body of the present invention is not limited to the following example.
[0145] The method for producing a zirconia sintered body according to this embodiment is as follows: Zirconia powder was added at 1.0 t / cm 2 More than 2.5t / cm 2 A process A of molding the molded body at a pressure of A step B of pre-sintering the molded body under normal pressure at a temperature of 1150° C. or higher and 1250° C. or lower for 1 hour or longer and 5 hours or shorter to obtain a pre-sintered body; and step C of sintering the pre-sintered body under conditions of a pressure of 50 MPa to 200 MPa, 1150° C. to 1250° C., and a time of 1 hour to 5 hours to obtain a sintered body.
[0146] In the method for producing a zirconia sintered body according to the present embodiment, first, zirconia powder is prepared. As the zirconia powder, the zirconia powder described in the section [Zirconia Powder] can be used.
[0147] Next, the zirconia powder was added at 1.0 t / cm 2 More than 2.5t / cm 2 The mixture is molded under the following pressure to obtain a molded body (Step A). A commercially available molder or cold isostatic pressing (CIP) can be used for molding. The zirconia powder may be temporarily molded in a molder and then pressed to obtain the final mold. The pressure is preferably 1.3 t / cm 2 More preferably, 1.5t / cm 2 That's all. The pressure is preferably 2.3 t / cm 2 Less than or equal to 2.2t / cm 2 The following is the result. The pressure is preferably 1.3 t / cm 2 More than 2.3t / cm2 Less than or equal to 1.5t / cm 2 More than 2.2t / cm 2 The following is the result.
[0148] Next, the molded body is pre-sintered under normal pressure at 1150° C. to 1250° C. for 1 hour to 5 hours to obtain a pre-sintered body (step B). In this embodiment, the molded body is pre-sintered under relatively low temperature conditions of 1150°C to 1250°C for 1 hour to 5 hours under normal pressure, so that a pre-sintered body with suppressed grain growth can be obtained. Since grain growth is suppressed, it is possible to obtain a zirconia sintered body with high translucency and high transparency. In particular, when the proportion of the cubic phase is high, the grain growth proceeds isotropically, and the growth of adjacent crystal grains is easily promoted. However, since the molded body is pre-sintered under relatively low conditions of normal pressure, 1150°C to 1250°C, and 1 hour to 5 hours, the grain growth can be suppressed even if the proportion of the cubic phase is high.
[0149] The preliminary sintering temperature is preferably 1160° C. or higher, and more preferably 1170° C. or higher. The preliminary sintering temperature is preferably 1245° C. or lower, more preferably 1240° C. or lower. The preliminary sintering temperature is preferably 1160°C or higher and 1245°C or lower, and more preferably 1170°C or higher and 1240°C or lower. The time for the preliminary sintering is preferably 1.2 hours or more, and more preferably 1.5 hours or more. The time for the preliminary sintering is preferably 4.7 hours or less, more preferably 4.5 hours or less. The time for the preliminary sintering is preferably 1.2 hours or more and 4.7 hours or less, and more preferably 1.5 hours or more and 4.5 hours or less. The preliminary sintering atmosphere may be air or an oxidizing atmosphere. The preliminary sintering may be performed under normal pressure, and pressurization is not particularly required.
[0150] Next, the pre-sintered body is sintered under conditions of a pressure of 50 MPa to 200 MPa, a temperature of 1150° C. to 1250° C., and a time of 1 hour to 5 hours to obtain a sintered body (step C). The main sintering is not particularly limited as long as the pressure is 50 MPa or more and 200 MPa or less and the temperature is 1150° C. or more and 1250° C. or less. For example, an apparatus employing a HIP (Hot Isostatic Pressing) method can be used. In step B, the molded body is pre-sintered under normal pressure at 1150°C to 1250°C for 1 hour to 5 hours, so that the particles of the zirconia powder are appropriately bonded together during the pre-sintering process, and the pores (gaps between the particles of the zirconia powder) in the molded body can be made into closed pores. In other words, the pre-sintering can change the pores from a state in which the pores are connected to each other (open pores) to isolated closed pores surrounded by bonds of the zirconia powder. Then, in step C, the provisionally sintered body, which has closed pores, is sintered under conditions of a pressure of 50 MPa to 200 MPa, 1150°C to 1250°C, and 1 hour to 5 hours, so that the closed pores can be almost completely eliminated. Specifically, the pressure applied in the sintering process compresses the closed pores to their minimum size, and the element diffusion (element flow) during the sintering process pushes the pores out of the sintered body, so that the closed pores can be almost completely eliminated. By removing the pores, the total light transmittance (translucency) and parallel light transmittance (transparency) can be improved. Furthermore, the pre-sintered body is sintered under conditions of a pressure of 50 MPa to 200 MPa, a temperature of 1150° C. to 1250° C., and a time of 1 hour to 5 hours, so that the relative sintered density can be 99.6% or more.
[0151] The pressure in the main sintering is preferably 55 MPa or more, and more preferably 60 MPa or more. The pressure in the main sintering is preferably 198 MPa or less, and more preferably 195 MPa or less. The pressure of the main sintering is preferably 55 MPa or more and 198 MPa or less, and more preferably 60 MPa or more and 195 MPa or less. The main sintering temperature is preferably 1160° C. or higher, and more preferably 1170° C. or higher. The main sintering temperature is preferably 1245° C. or lower, more preferably 1240° C. or lower. The main sintering temperature is preferably 1160°C or higher and 1245°C or lower, and more preferably 1170°C or higher and 1240°C or lower. The time for the main sintering is preferably 1.2 hours or more, and more preferably 1.5 hours or more. The time for the main sintering is preferably 4.7 hours or less, more preferably 4.5 hours or less. The time for the main sintering is preferably 1.2 hours or more and 4.7 hours or less, and more preferably 1.5 hours or more and 4.5 hours or less.
[0152] After the preliminary sintering in step B, the temperature is usually cooled to 40°C or less, and then the main sintering is performed (step C is performed). This is because step B is sintering at normal pressure, whereas step C is sintering including pressure, and therefore the sintering equipment used is different. That is, after the preliminary sintering, the product is cooled and removed from the equipment in which the preliminary sintering was performed, and then placed in an equipment for the main sintering, and the main sintering is performed. In order to perform the main sintering, the product is usually cooled to 40°C or less after the preliminary sintering in step B, and then heated again to perform the main sintering. However, the present invention is not limited to this example, and for example, when steps B and C are performed in the same equipment, the main sintering may be performed directly without cooling after the preliminary sintering in step B.
[0153] The method for producing a stabilized zirconia sintered body according to this embodiment has been described above. EXAMPLES
[0154] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. Note that the zirconia powder and zirconia sintered body in the examples and comparative examples contain 1.3 to 2.5 mass % of hafnium oxide as an inevitable impurity relative to zirconium oxide (calculated by the following formula (X)). <Expression(X)> ([Mass of hafnium oxide] / ([Mass of zirconium oxide]+[Mass of hafnium oxide]))×100(%)
[0155] [Preparation of zirconia powder] (Production Example 1) 213 g of a 25% by mass aqueous solution of sodium sulfate and 450 g of an aqueous solution of zirconium oxychloride (acid concentration: 1N) equivalent to 16% by mass in terms of ZrO2 were separately heated to 95°C (step 1). 2- The heated aqueous solutions were brought into contact with each other for 2 minutes so that the ZrO2 mass ratio was 0.50 (step 2). Next, the obtained reaction liquid containing basic zirconium sulfate was kept at 95° C. for 4 hours for aging, thereby obtaining basic zirconium sulfate (step 3). Next, after the aged solution was cooled to room temperature, an aqueous solution of yttrium chloride having a concentration of 10 mass % in terms of Y2O3 was added thereto so that the Y2O3 content was 4.1 mol %, and the solution was mixed uniformly (step 4). Next, a 25% by mass aqueous solution of sodium hydroxide was added to the resulting mixed solution to neutralize it until the pH became 13 or higher, thereby forming a hydroxide precipitate (step 5). The obtained hydroxide precipitate was filtered and thoroughly washed with water, and the obtained hydroxide was dried for 24 hours at 105° C. The dried hydroxide was heat-treated in air at 960° C. (calcination temperature) for 2 hours to obtain an unpulverized zirconia-based powder (yttria-stabilized zirconia-based powder) (step 6). Alumina powder having an average primary particle size of 0.1 μm was added to the unpulverized yttria-stabilized zirconia powder obtained, in an amount of 0.1 mass% relative to the yttria-stabilized zirconia powder, and the mixture was pulverized and mixed for 40 hours in a wet ball mill using water as a dispersion medium. Zirconia beads φ5 mm were used for pulverization. The zirconia slurry obtained after pulverization was dried at 110° C. to obtain the zirconia powder according to Example 1. Specifically, the above operation was carried out using the apparatus as explained with reference to FIG.
[0156] (Production Example 2 to Production Example 16) Zirconia powders of Production Examples 2 to 16 were obtained in the same manner as Production Example 1, except that the amount of yttrium chloride aqueous solution added was changed so that the content of Y2O3 was the amount shown in Table 1, and / or the content of alumina powder was changed so that the content was the amount shown in Table 1.
[0157] (Production Example 17) The zirconia powder of Production Example 17 was obtained in the same manner as Production Example 1, except that the amount of yttrium chloride aqueous solution added was changed so that the content of Y2O3 was the amount shown in Table 1, and calcium carbonate (CaCO3) was added at the same timing as the addition of the yttrium chloride aqueous solution so that the amount was 0.5 mol% in terms of CaO.
[0158] (Example 18) The zirconia powder of Production Example 18 was obtained in the same manner as Production Example 1, except that the amount of yttrium chloride aqueous solution added was changed so that the Y2O3 content was the amount shown in Table 1, and a 10 mass% ytterbium chloride aqueous solution was added at the same timing as the addition of the yttrium chloride aqueous solution so that the content was 0.3 mol% in terms of Yb2O3.
[0159] (Example 19) The zirconia powder of Production Example 19 was obtained in the same manner as Production Example 1, except that the amount of yttrium chloride aqueous solution added was changed so that the Y2O3 content was the amount shown in Table 1, and a 10 mass% erbium chloride aqueous solution was added at the same timing as the addition of the yttrium chloride aqueous solution so that the content was 0.2 mol% in terms of Er2O3.
[0160] [Table 1]
[0161] [Preparation of zirconia sintered body] <1. Molded body> First, the zirconia powder of the manufacturing example was molded by cold isostatic pressing (CIP) to obtain a molded body. The molding pressure was as shown in Table 1. At this time, the relative molded density of the molded body was calculated by the following (3). The results are shown in Table 1.
[0162] <2. Pre-sintered body> Next, the molded body was pre-sintered under normal pressure (1 atm) at the pre-sintering temperature and time shown in Table 2 to obtain a pre-sintered body. The pre-sintered bodies of Examples 1 to 11 were obtained by pre-sintering the molded bodies of Production Examples 1 to 11, respectively. The pre-sintered body of Example 12 was obtained by pre-sintering the molded body of Production Example 5. The pre-sintering conditions of Examples 5 and 12 were different (the molding conditions were the same). The pre-sintered bodies of Comparative Examples 1 to 5 were obtained by pre-sintering the molded bodies of Production Examples 12 to 16, respectively. The pre-sintered body of Comparative Example 6 was obtained by pre-sintering the molded body of Production Example 1. Example 1 and Comparative Example 6 had different pre-sintering conditions (the molding conditions were the same). The pre-sintered body of Comparative Example 7 was obtained by pre-sintering the molded body of Production Example 2. Example 2 and Comparative Example 7 had different pre-sintering conditions (the molding conditions were the same). The pre-sintered bodies of Examples 13 to 15 were obtained by pre-sintering the molded bodies of Production Examples 17 to 19, respectively. The relative sintered density (density of the pre-sintered body) of the obtained pre-sintered body was determined as follows. The results are shown in Table 2.
[0163] [Relative sintered density] The relative sintered density is represented by the following formula (1). Relative sintered density (%) = (sintered density / theoretical sintered density) × 100 (1) Here, the theoretical sintered density (ρ0) is a value calculated by the following formula (2-1). ρ0=100 / [(Y / 3.987)+(100-Y) / ρz]···(2-1) Here, ρz is a value calculated by the following formula (2-2). ρz = [124.25(100-X) + [molecular weight of stabilizer] × X] / [150.5(100+X)A 2 C]···(2-2) Here, the molecular weight of the stabilizer is 225.81 for Y2O3. Additionally, X and Y are the stabilizer concentration (mol %) and the alumina concentration (wt %), respectively, and A and C are values calculated by the following formulas (2-3) and (2-4), respectively. A=0.5080+0.06980X / (100+X)...(2-3) C=0.5195-0.06180X / (100+X)...(2-4) In formula (1), the theoretical sintered density varies depending on the powder composition. For example, the theoretical sintered density of yttria-containing zirconia is 6.117 g / cm when the yttria content is 2 mol%. 3 , 3 mol% is 6.098 g / cm 3 , 5.5 mol% is 6.051 g / cm 3 (when Al2O3 = 0 wt%). In addition, the theoretical sintered density (ρ1) when other components (stabilizers, colorants, etc.) other than alumina are included is: ρ1=100 / [(Z / V)+(100-Z) / ρ0]···(2-5) Z is the concentration of other components other than alumina (wt%), and V is the theoretical density of other components other than alumina (g / cm 3 ). The theoretical density of the other components other than alumina is 9.17 g / cm for Yb2O3. 3 , Er2O3 is 8.64g / cm 3 , CeO2 is 7.22g / cm 3 , Sc2O3 is 3.86g / cm 3 , Nd2O3 is 7.24g / cm 3 , La2O3 is 6.51g / cm 3 , Tb2O3 is 7.81g / cm 3 , CaO is 3.34g / cm 3 , Fe2O3 is 5.24g / cm 3 , ZnO is 5.61 g / cm 3, MnO2 is 5.03g / cm 3 , CoO is 6.10g / cm 3 , Cr2O3 is 5.22g / cm 3 , TiO2 is 4.23g / cm 3 , CuO is 6.31g / cm 3 , V2O5 is 3.36g / cm 3 Let us assume that. The sintered density is measured by the Archimedes method.
[0164] [Relative molding density] Relative molded density (%) = (molded density / theoretical sintered density) × 100 (3) Here, the theoretical sintered density (ρ0) is a value calculated by the above formula (2-1).
[0165] <3. Sintered body> Next, the pre-sintered body was sintered at the pressure, temperature and time shown in Table 2 to obtain a sintered body. The sintering was performed using an apparatus employing the hot isostatic pressing (HIP) method.
[0166] [Relative sintered density] The relative sintered density of the sintered body was measured in the same manner as in the measurement of the relative sintered density of the pre-sintered body. The results are shown in Table 2.
[0167] [Table 2]
[0168] [Average grain size] The average crystal grain size was determined using the SEM observation image of the sintered body sample obtained by SEM observation. The sample for SEM observation was prepared based on JIS R1633. The SEM observation image was obtained at a magnification such that the number of crystal grains in one field of view was 150 or more. The average crystal grain size of the zirconia sintered body of the examples and comparative examples was determined by the following formula according to the method described in J. Am. Ceram. Soc., 52 [8] 443-6 (1969), which is measured by scanning electron microscope observation of the polished and etched surface of the sintered body. D=1.56L D: Average grain size L: Average length of a particle crossing any straight line
[0169] [Identification of crystalline phases] The X-ray diffraction spectrum of the zirconia sintered body was obtained using an X-ray diffractometer ("RINT2500" manufactured by Rigaku) under the following measurement conditions. <Measurement conditions> Measurement equipment: X-ray diffraction equipment (Rigaku, RINT2500) Source: CuKα source Sampling interval: 0.02° Scan speed: 2θ=1.0° / min Divergence slit (DS): 1° Divergence vertical limit slit: 5mm Scattering slit (SS): 1° Receiving slit (RS): 0.3 mm Monochrome receiving slit: 0.8 mm Tube voltage: 50kV Tube current: 300mA Scanning speed: 2θ=10~80°: 4° / min 2θ=72~76°: 1° / min
[0170] The crystal phases were then identified from the X-ray diffraction spectrum. The ratio of each crystal phase contained in the zirconia sintered body was calculated using the following formula. Monoclinic fraction (%) = (Im(111) + Im(11-1)) / (Im(111) + Im(11-1) + It(101) + Ic(111)) × 100 Tetragonal phase ratio (%)=(100%-monoclinic phase (%))×((It(004)+It(220) / (It(004)+It(220)+Ic(004))×100 Cubic phase ratio (%)=(100%-monoclinic phase (%))×((Ic(004) / (It(004)+It(220)+Ic(004))×100 Here, Im(111) is the diffraction intensity of (111) in the monoclinic phase, and Im(11-1) is the diffraction intensity of (11-1) in the monoclinic phase. It(101) is the diffraction intensity of (101) in the tetragonal phase, It(220) is the diffraction intensity of (220) in the tetragonal phase, and It(004) is the diffraction intensity of (004) in the tetragonal phase. Ic(004) is the diffraction intensity of (004) in the cubic phase, and Ic(111) is the diffraction intensity of (111) in the cubic phase. The monoclinic phase of zirconia was distinguished from the tetragonal and cubic phases at 2θ=26-36° in the XRD spectrum. The tetragonal and cubic phases were distinguished at 2θ=72-76° in the XRD spectrum. The cubic phase may be distorted depending on the amount of stabilizer added and the manufacturing method, and the peak position may shift, but in this example, the peak between (004) and (220) of the tetragonal phase was taken as the peak of the cubic phase and calculated.
[0171] [Total light transmittance] The total light transmittance of the zirconia sintered bodies of the examples and comparative examples was measured using a spectroscopic haze meter (device name: SH-7000, manufactured by Nippon Denshoku Industries Co., Ltd.) with a D65 light source according to a method conforming to JIS K7361. The measurement samples were polished on both sides and adjusted to a thickness of 1 mm. The results are shown in Table 3.
[0172] [Parallel light transmittance] The parallel light transmittance of the zirconia sintered bodies of the examples and comparative examples was calculated from the total light transmittance obtained by JIS K7361-1 and the diffuse transmittance Td described in JIS K7136:2000 according to the following formula. [Parallel light transmittance (%)] = [Total light transmittance (%)] - [Diffuse transmittance Td (%)] Here, [diffuse transmittance Td (%)] is [total light transmittance (%)] × [haze (%)] × 100 -1 This is the value calculated as follows. [Haze (%)] was measured in accordance with JIS K7136:2000. The measurement samples were polished on both sides to adjust the thickness to 1 mm. The results are shown in Table 3.
[0173] [Monoclinic phase ratio after hydrothermal treatment at 134℃, 0.3MPa, 75 hours] First, the zirconia sintered bodies of the examples and comparative examples were subjected to hydrothermal treatment at 134°C and an absolute pressure of 0.3 MPa (underwater atmosphere) for 75 hours. Thereafter, the monoclinic fraction contained in the crystal phase of the zirconia sintered body after the hydrothermal treatment was determined. The method for determining the monoclinic fraction of the zirconia sintered body after the hydrothermal treatment was the same as that described in the section [Identification of the crystal phase]. The results are shown in Table 3.
[0174] [3-point bending strength] The three-point bending strength of the zirconia sintered bodies of the Examples and Comparative Examples obtained above was measured in accordance with the three-point bending strength standard of JIS R 1601. The results are shown in Table 3.
[0175] [Toughness] The toughness measurement by the IF method was performed with a load of 5.0 kgf (49.0 N) in accordance with JIS R1607 (Room temperature fracture toughness test method for fine ceramics). Using a Vickers hardness tester, seven indentations with a rectangular shape were selected to determine the toughness, and the toughness value was calculated by averaging the toughness values of the five points excluding the smallest and largest values. However, if the indentation did not extend from the indentation, it was deemed invalid, and the indentation with four cracks extending from the tip of the rectangle was used. Each toughness value was calculated by the following formula. Kc = 0.018 × Hv × a 0.5 ×[(ca) / a] -0.5 ×(Hv / E) -0.4 Kc, Hv, a, c, and E have the following meanings. When calculating a and c, the indentation length on the X and Y axes and the crack length on the X and Y axes are as shown in Figure 2. Kc: Toughness value [MPa m 0.5 ] Hv: Vickers hardness [GPa] a: Half the average value of the indentation length on the X and Y axes [μm] c: Half the average crack length on the X and Y axes [μm] E: Young's modulus [GPa] The Vickers hardness was measured in accordance with JIS R 1610 (hardness test method for fine ceramics). The Vickers hardness was calculated using the following formula. Hv = 0.001854 × [F / d 2 Sv] F and d have the following meanings. The X-axis indentation length and Y-axis indentation length used to calculate d are as shown in Figure 2. Hv: Vickers hardness [GPa] F: Test force [N] d: Average value of X-axis indentation length and Y-axis indentation length [mm] The Young's modulus used was 210 GPa, which is known as the value of common yttria-stabilized zirconia.
[0176] [Table 3]
Claims
1. The stabilized zirconia includes zirconia and a stabilizer. The content of the stabilized zirconia is 80% by mass or more when the entire zirconia sintered body is 100% by mass, The stabilizer is Y 2 O 3 Including, The Y in the stabilized zirconia 2 O 3 The content of is more than 4.0 mol% and not more than 6.5 mol% in terms of oxide, The average crystal grain size is 100 nm or more and 200 nm or less, The monoclinic fraction is 0.5% or less, The tetragonal fraction is 20.0% or more and 96.0% or less, The cubic fraction is 4.0% or more and 80.0% or less, The relative sintered density is 99.6% or more, A zirconia sintered body having a total light transmittance of 45% or more and 60% or less at a thickness of 1 mm.
2. The Y in the stabilized zirconia 2 O 3 The zirconia sintered body according to claim 1, characterized in that the content of exceeds 5.2 mol% in terms of oxide.
3. The tetragonal fraction is 20.0% or more and 60.0% or less, 2. The zirconia sintered body according to claim 1, characterized in that the cubic phase fraction is 40.0% or more and 80.0% or less.
4. The Y in the stabilized zirconia 2 O 3 The content of exceeds 5.2 mol% in terms of oxide, The tetragonal fraction is 20.0% or more and 60.0% or less, 2. The zirconia sintered body according to claim 1, characterized in that the cubic phase fraction is 40.0% or more and 80.0% or less.
5. Al for the entire zirconia sintered body 2 O 3 The zirconia sintered body according to any one of claims 1 to 4, characterized in that it contains 0.15 mass% or less of
6. The zirconia sintered body according to any one of claims 1 to 4, characterized in that the parallel light transmittance at a thickness of 1 mm is 7.0% or more and 30.0% or less.
7. The zirconia sintered body according to any one of claims 1 to 4, characterized in that the three-point bending strength is 500 MPa or more and 1000 MPa or less.
8. The toughness value measured by the IF method is 2.7 MPa m 0.5 5.0MPa・m or more 0.5 The zirconia sintered body according to any one of claims 1 to 4, characterized in that:
9. Zirconia powder was added at 1.0 t / cm 2 More than 2.5t / cm 2 A step A of molding the molded body at a pressure of A step B of pre-sintering the molded body under normal pressure at a temperature of 1150° C. or higher and 1250° C. or lower for 1 hour or longer and 5 hours or shorter to obtain a pre-sintered body; The temporary sintered body is sintered under conditions of a pressure of 50 MPa to 200 MPa, 1150 ° C. to 1250 ° C., and 1 hour to 5 hours to obtain a sintered body. The method for producing a zirconia sintered body according to any one of claims 1 to 4, further comprising: a step C of sintering the temporary sintered body under conditions of a pressure of 50 MPa to 200 MPa, 1150 ° C. to 1250 ° C., and 1 hour to 5 hours.
Citation Information
Patent Citations
ZrO2 SINTERED COMPACT AND ITS MANUFACTURING METHOD, MEMBER OF CRUSHER, AND CRUSHER
JP2006298711A
Translucent yttria-containing zirconia sintered compact, manufacturing method and utilization of the same
JP2008222450A
Zirconia sintered body, and manufacturing method thereof
JP2014218421A
Zirconia sintered body, zirconia powder, and method for producing zirconia sintered body
WO2023171542A1
Zirconia powder, sintered zirconia object, and method for producing sintered zirconia object
WO2023190119A1